Fuels with low octane number: water injection as knock control method. Issue 2 (February 2019) - Brusca, S.; Galvagno, A.; Lanzafame, R.; Mauro, S.; Messina, M.
Abstract: The present paper deals with the study of water effect on the combustion of fuels with low Octane Number in Internal Combustion Engines. In particular, this study was carried out using a variable volumetric compression ratio CFR fuel engine. ASTM Standards for Motor and Research methods were followed to determine fuels and fuel-water mixture Octane Number. CFR fuel engine intake manifold was modified to install water injection. Different water/fuel mass ratios were used and Research and Motor Methods Octane Number and pollutant emissions were measured. In particular, water to fuel mass flow ratio was imposed from 0 to 1.5. Increasing the water/fuel mass ratio an increment in octane number was registered and this behaviour is evident for each base octane number studied. At the same time a reduction in the NOx emissions was registered due to both in-cylinder temperature reduction and water chemical interaction with NOx . Analysing in-cylinder pressure traces highlighted that water presence reduces pressure oscillation within the cylinder engine. On the basis of the results it is possible to state that water is able to control detonation in the fuel combustion and an increment of the octane number is registered.